Service Delivery gaps and its 'impact on customer's perception towards service quality at Spencers Retailers - Chandra, P. Sathish (Gyan Management Journal, 2016)
One of the prominent issues faced by all retail companies is to manage the customer expectations because service received is compared with what was expected, while arriving at a judgment or perception of satisfaction. The marketer's dilemma is that if he pitches high, creating high expectations, there would be likelihood that they may not meet them, and leave the customer unhappy However, ifhe pitches too low, the customer may not try his service al all as he many not getattractec. enough to it. There is a fine balance between hype and substance that the service provider shoulc. maintain while performing his marketing effort. As quality is a relative concept, a retailer may no· always understand what features connote high quality to customers. The firm's lack of understanding may affect quality perceptions of customers. Delivery gaps will have an impact on the evaluation o· service quality. If there is no gap it means consumer expectation. The following study is to understan and measure the quality gaps in Spence rs retail services offered to the customers.
Keywords: Customer Satisfaction; Delivery gaps; Quality; Spencers; Service; SERVIQUAL